Analysis of Theatre as a Communication Media: Exploring the Role of Theatre in Communication (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Theatrical communication is a dramatic art form. The trying to impart or sharing of informationby talking, trying to write, or using some other medium (Cambridge Phonetic spellings) is whatcommunication entails. Humanity's basic inclination is to perform on stage. We gather knowledge fromour surroundings. Information = knowledge. So we collect a lot of data or sensory data using our fivesenses clear view, having to hear, odour, grasp, and flavours. We express ourselves in such a mannerthat we encounter anything from our globe through theatre. Theatre is an experience. Theatre alsoinforms. Audiences become imaginative as actors share their experiences or details. Viewers reminisceabout their own life experience while watching the theatre. It is the most fundamental relationshipbetween the actor or entertainer and the viewing public.This research is a modest attempt to perceive thetheatre as a communication media that can considerably add to the potential to efficientlyperformvarious communication functions. It also aims to discuss the importance of addressing communicationstudies from an Indian viewpoint, highlighting parallels between Aristotle's Poetics and Rhetoric andBharata's Ntyasstra.